Contribution to the clinic and anatomy of acute epidemic hepatitis Abancay - Encinas, E. (1956)
In the years 1952-1955 we had the opportunity to observe the development of an epidemic of fulminant infectious hepatitis in the city of Abancay, capital of the department of Apurimac (Peru), preferably in children, Aboriginal or not, the city and its environs. Anatomical material from some of these cases was sent to the Pathology Laboratory, Faculty of Medicine, the Professor, Dr. Peter Weiss, made the histological diagnosis of the disease. Shortly afterwards, and the good offices of Dr. Ramón Montenegro the Bureau of Lima, part of that material was sent to the Instituto Oswaldo Cruz, Rio de Janeiro, where the Head of Virus Section of Pathology, Dr . Madureira Pará, confirmed the diagnosis of infectious hepatitis.